Perancangan Sistem Ujian Online dengan Data Base Mysql di SMK N 9 Padang Kelas X Semester Genap Tahun Ajaran 2021/2022 - Pedi Rianda; Nisa Vebriani; Ambiyar Ambiyar; Deviana Rindhani (Journal on Education, 2023)
This study aims to determine the Validity, Practicality and Effectiveness of designing an online exam system with the mysql database at SMK Negeri 9 Padang class X Even Semester 2021/2022 Academic Year. This study uses research development methods (research & development). The research subjects were 30 people. The research model used is the 4D development research model consisting of 4 main stages, namely: Define Design, Develop and Disseminate. The results showed that: The results of the validity test by the experts as a whole the validator test assessment of the Web-Based Online Examination Website in class X students of SMK Negeri 9 Padang was 96.00%, so the validity level can be interpreted as very valid to use. The results of the practicality test assessment as a whole practicality assessment of the Web-Based Online Examination Website in class X students of SMK Negeri 9 Padang 89.31%, so that the level of practicality can be interpreted as very practical to use. The results of the overall effectiveness test assessment of the effectiveness of the Web-Based Online Examination Website for class X students of SMK Negeri 9 Padang amounted to 87.43% so that the level of effectiveness can be interpreted to be used very effectively.